The methodology of documenting cultural heritage sites using photogrammetry, UAV and 3D printing techniques: The case study of Asinou Church in Cyprus - Themistocleous, Kyriacos; Ioannides, Marinos; Agapiou, Athos; Hadjimitsis, Diofantos G. (My University, 2015)
.As the affordability, reliability and ease-of-use of Unmanned Aerial Vehicles (UAV) advances, the use of aerial surveying for cultural heritage purposes becomes a popular choice, yielding an unprecedented volume of high-resolution, geo-tagged image-sets of historical sites from above. As well, recent developments in photogrammetry technology provide a simple and cost-effective method of generating relatively accurate 3D models from 2D images. These techniques provide a set of new tools for archaeologists and cultural heritage experts to capture, store, process, share, visualise and annotate 3D models in the field. This paper focuses on the methodology used to document the cultural heritage site of Asinou Church in Cyprus using various state of the art techniques, such as UAV, photogrammetry and 3D printing. Hundreds of images of the Asinou Church were taken by a UAV with an attached high resolution, low cost camera. These photographic images were then used to create a digital 3D model and a 3D printer was used to create a physical model of the church. Such a methodology provides archaeologists and cultural heritage experts a simple and cost-effective method of generating relatively accurate 3D models from 2D images of cultural heritage sites.
Keywords: 3D models; Cultural heritage; DEM; UAV